Trait Evaluation of 9 Bird’s Eye Chili (Capsicum frutescens L.) Hybrids on Coastal Area - Emilda Tri Mauli; Rustikawati; Catur Herison; Marulak Simarmata; Merakati Handajaningsih (BPFP Universitas Bengkulu, 2025)
Soil in coastal areas are less suitable for agriculture due to various constraints causing low soil fertility. Until now, there has been no available bird’s eye chili variety tolerant to coastal stress conditions. This research aims to characterize nine bird’s eye chili hybrids grown on coastal land. The research was conducted on coastal land in Kuala Alam Nusa Indah, Ratu Agung District, Bengkulu, from August 2024 to February 2025. The experiment was arranged in a Randomized Complete Block Design (RCBD) with three replications. The traits observed consisted of both quantitative and qualitative variables related to bird’s eye chili growth and yield. Quantitative data were analyzed using ANOVA at a 5% and 1% significance level, followed by a Scott-Knott test, α = 5%, to assess data grouping. Qualitative data were descriptively analyzed by comparing with reference to the descriptor for capsicum. The results showed that the tested hybrids differed in all traits. The results showed that the hybrid H3 (A11 × A7) showed the highest production potential with long fruit and large yields despite slower days to flower and a small stem diameter, while hybrid H8 (A39 × A29) excelled more equally in most traits, including fast days to flower, highest plant height and dichotomous height, large stem diameter, large number of branches, high leaf greenness, long fruit with large diameter, and a high fruit weight. Overall, H3 and H8 bird’s eye chili hybrids are potential to be adapted varieties to coastal areas with improvements in several characteristics. Full text pdf